Pengaruh Investasi Kelapa Sawit Dan Tenaga Kerja Terhadap PDRB pada Sub Sektor Perkebunan di Kabupaten Kutai Timur - Ariyanto, Bagus (Faculty of Economics and Business Mulawarman University, 2017)
The purpose of this research is to know the influence of investment of palm oil and labor Force to gross domestic product of estate sector in East Kutai Regency and to know the dominant influence variable to gross domestic product of plantation sector in East Kutai Regency. The analysis tool used in this research is Multiple Linear Regression. Hypothesis testing using t test and F test. The analysis shows that investment has a significant and positive effect and the work force has a positive effect on the gross domestic product in the plantation sector.Keywords: Investment, Labor Force, Gross Regional Domestic Product